The role of green tea and green coffee extract, empagliflozin and metformin treatment on FGF23 mRNA expression in calcified aorta tissue in metabolic syndrome model Sprague-Dawley rat - Kurniawan, Ary; Mohammad Saifur Rohman; Yogibuana, Valerinna (Heart Science Journal, 2026)
Background: Metabolic syndrome (MetS), encompassing dyslipidemia, glucose intolerance, hypertension, and central obesity, increases cardiovascular risk, including vascular calcification. Fibroblast growth factor 23 (FGF23), a bone-derived regulator of phosphate and vitamin D, is implicated in vascular calcification in kidney disease, but its role in MetS-related calcification is unclear. Objective: To determine if MetS promotes vascular calcification and alters aortic FGF23 mRNA expression in rats, and to assess effects of green tea/coffee extract, metformin, and empagliflozin on FGF23 mRNA modulation. Methods: Twenty-five Sprague-Dawley rats were divided into five groups: negative control, MetS (induced via high-fat/high-sucrose diet and streptozotocin), and three treatment groups (green tea/coffee extract, metformin 500mg/kg, empagliflozin 30mg/kg). Aortic calcification (hematoxylin-eosin staining) and FGF23 mRNA expression (qRT-PCR) were analyzed after 9 weeks. ANOVA with LSD post-hoc tests was used. Results: This study found MetS induction promoted vascular calcification. FGF23 mRNA expression increased in the MetS group compared to controls, though not statistically significant. All treatments reduced FGF23 mRNA levels modestly, but effects lacked statistical significance (p = 0.851–0.989), likely due to complex, tissue specific regulation of FGF23. Conclusion: Metabolic disturbances in MetS may prime vascular tissues for calcification without significantly altering local FGF23 mRNA expression. Interventions targeting oxidative stress, inflammation, or glucose metabolism could modulate FGF23-related pathways, warranting further investigation into the underlying signaling mechanisms.